Trans-orbital sonography of the optic nerve in multiple sclerosis - Seyedehnarges Tabatabaee; Negin Eissazade; Zahra Mirzaasgari; Seyed Mosa Tabatabaee; Leila Raeesmohammadi; Mohammad Reza Motamed (PLoS ONE, 2025)
Background Trans-orbital sonography (TOS) has emerged as a non-invasive tool for detecting optic nerve damage by measuring optic nerve diameter (OND) and optic nerve sheath diameter (ONSD). Objective This study aimed to assess OND, ONSD, and their ratio in patients with MS and healthy controls, and to explore their potential associations with clinical and paraclinical parameters. Methods In this comparative cross-sectional study (January 2022-September 2022), we enrolled adult (≥ 18 years) patients with MS, diagnosed based on the 2017 revised McDonald criteria, who were on stable disease-modifying drugs, and healthy volunteers without neurological or ophthalmic conditions. Sonographic assessments of OND and ONSD were performed using an M-Turbo ultrasound machine with an 8-MHz linear probe. Results A total of 56 patients with MS and 60 healthy controls were included. OND, ONSD, and OND/ONSD were significantly smaller in patients with MS, even after adjusting for age (p < 0.001). The reductions in OND and ONSD were more pronounced in individuals with a history of optic neuritis, while the OND/ONSD ratio remained unaffected by op. No significant associations were observed between OND or ONSD values and age, sex, MS type, EDSS score, disease duration, DMD, or cervical or thoracic cord lesions. However, infratentorial lesions were associated with smaller right ONSD (p = 0.017). Conclusions Reduced OND and ONSD in patients with MS, especially in those with prior optic neuritis, suggest that sonographic evaluation may reflect subclinical optic nerve atrophy. These findings support the utility of OND and ONSD as potential structural markers in MS, though further longitudinal and multimodal studies are needed to confirm their diagnostic and prognostic value.